Network Economics : Principles - Strategies - Competition Policy - Knieps, Günter (Springer Texts in Business and Economics,, 2015)
This textbook on network economics provides essential microeconomic instruments for the analysis of network sectors like telecommunications, transport or energy. Network-specific characteristics emerge both on the cost side and benefit side, requiring network providers to develop innovative entrepreneurial competition strategies for costing, pricing, and investment. From a competition policy perspective, a number of interesting questions arise: In which parts of networks is competition functional? In contrast, where is an abuse of market power to be expected? What is the division of labor between cartel authorities and regulatory agencies? The book develops an analytical framework for all network industries which allows readers to study entrepreneurial strategies as well as regulation and competition policies for network industries.